2019
DOI: 10.3390/w11091912
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Iron and Manganese from Groundwater Samples in Ghana by Zeolite Y Synthesized from Bauxite and Kaolin

Abstract: Ground water samples from residential homes in three Regions of Ghana: Central, Greater Accra and Ashanti, were analyzed for iron and manganese contamination. The samples were exposed to characterized zeolite Y by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy, Fourier transformed-infrared spectroscopy and thermos gravimetric-differential thermal analysis. Zeolite Y is able to remove 98% of iron and 97% of manganese within an hour. The adsorption of both iron and manganes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 35 publications
0
24
0
3
Order By: Relevance
“…The analysis of research results presented in Figure 6 a,b showed that, in the subsequent stage of water purification, during filtration on a catalytic-oxidative sand filter bed, manganese compounds were removed to the greatest extent, from 70.82 (following PAXXL1911 coagulation) to 74.55% (following PAXXL10 coagulation), which was to be anticipated due to the presence of manganese (IV) oxide in the catalytic-oxidative filter bed, which has adsorption abilities in regards to many metals, also including Mn(II), but, above all, plays the role of an oxidizing agent of Mn(II) ions to Mn(III), which are then oxidized with dissolved oxygen to Mn(IV) and precipitated from water as MnO 2 ·H 2 O [ 37 ]. Irrelevant of the type of tested coagulant, the concentration of manganese in water after filtration through a catalytic-oxidative sand filter bed, was 0.02 mg Mn /L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of research results presented in Figure 6 a,b showed that, in the subsequent stage of water purification, during filtration on a catalytic-oxidative sand filter bed, manganese compounds were removed to the greatest extent, from 70.82 (following PAXXL1911 coagulation) to 74.55% (following PAXXL10 coagulation), which was to be anticipated due to the presence of manganese (IV) oxide in the catalytic-oxidative filter bed, which has adsorption abilities in regards to many metals, also including Mn(II), but, above all, plays the role of an oxidizing agent of Mn(II) ions to Mn(III), which are then oxidized with dissolved oxygen to Mn(IV) and precipitated from water as MnO 2 ·H 2 O [ 37 ]. Irrelevant of the type of tested coagulant, the concentration of manganese in water after filtration through a catalytic-oxidative sand filter bed, was 0.02 mg Mn /L.…”
Section: Resultsmentioning
confidence: 99%
“…After the coagulation process with PAXXL1911 coagulant with an alkalinity of 85% containing iron additives in its composition, the highest values of the Pearson coefficient were confirmed between iron (III) and dissolved organic substances containing aromatic rings, as well as between turbidity and iron (III), and also between the color measured at a wavelength of 340 nm and DOC and UV 254 . According to Kwakye-Awuah et al [ 37 ] the iron ion pollution in groundwater may interact with the dissolved constituents, such as dissolved organic carbon (DOC), present as a humic-like material. These interactions lead to complex formations and to potential solid precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…Water for the preparation of solutions was tap water purified by a five-stage reverse osmosis system (Aqualive, s.r.o., Košice, Slovakia). The equilibrium experiments were carried out with a series of PET flasks containing 0.1 dm 3 (V) of metal ion solution of different initial concentrations (C 0 = 1 to 4000 mg.dm −3 ) prepared from iron sulphate and a fixed dosage of sorbent (C a = 1 g.dm −3 ) which were agitated for 2 h in a rotary shaker at 3.33 s −1 , with a temperature control at 25 • C, what was sufficient for the metal ions adsorption to reach an equilibrium, based on previous studies [6,8,[10][11][12][13]15,16]. The initial pH of the solution was not adjusted.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of temperature on the sorption capacity is also significant as the maximum sorption capacity increases with increasing temperature [10] and this influence also depends on the nature of the process if it is endothermic or exothermic [11]. These and many other papers [12][13][14][15][16] only studied the sorption equilibrium and kinetics and, in some cases, influence of additives, in aqueous phase. If the solid phase was studied, only the material before the adsorption was characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Oleh karena itu dibutuhkan upaya untuk meningkatkan daya serap kaolin. Salah satu upaya peningkatan daya serap kaolin sebagai adsorben dapat dilakukan dengan memodifikasikanya menjadi metakaolin (fase metastabil dari kaolin) dilanjutkan dengan aktivasi dengan basa sehingga membentuk struktur menyerupai zeolit [18] [19]. Metakaolin merupakan mineral lempung kaolin dalam bentuk terdehidrasi.…”
Section: Pendahuluanunclassified